Ownership Structure and Firm Performance: The Moderating Effect of Audit Quality (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Malaysia, like many other countries, has experienced several corporate scandals that have raised concerns regarding the credibility and integrity of financial reporting. The study examines whether audit quality plays a key role in reducing the impact of management’s entrenchment activities, increases the credibility of the financial report, hence improving the overall firm performance. The data are derived from 540 firm year observations collected over five years (2019-2023). To analyse the data, the Panel Corrected Standard Error is used. The findings show that firms audited by big4 together with the existence of ownership structure (family, government and foreign) perform better. This result indicated that external audit quality is an effective corporate governance mechanism that is likely to monitor family, government and foreign corporate decisions. The result gives understanding to investors, regulators, and financial analysts that the moderating effect of audit quality on the ownership structure would strengthen the corporate board monitoring and deter management from engaging in perpetual unethical practice and improve the overall firm’s performance.